2017
DOI: 10.1038/leu.2016.395
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-delta promotes survival of chronic lymphocytic leukemia cells in energetically unfavorable conditions

Abstract: Targeting the mechanisms that allow chronic lymphocytic leukemia (CLL) cells to survive in harsh cancer microenvironments should improve patient outcomes. The nuclear receptor peroxisome proliferator activated receptor delta (PPARδ) sustains other cancers, and in silico analysis showed higher PPARD expression in CLL cells than normal lymphocytes and other hematologic cancers. A direct association was found between PPARδ protein levels in CLL cells and clinical score. Transgenic expression of PPARδ increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…which coactivate NF-kB-dependent survival signaling in CLL (Minami et al, 2010) and the GATA family, known to prime hematopoietic stem cells (HSCs) toward the lymphoid lineage and to increase self-renewal of the stem cells in CLL (Kikushige et al, 2011). We also found the EGR family, which are implicated in aberrantly hypomethylated CpG sites in CLL (Oakes et al, 2016); Gli1, which is part of the Hedgehog signaling pathway that regulates apoptosis, thereby supporting survival of M-CLL cells (Kern et al, 2015); and PPARD, which has recently been linked to M-CLL through its effect on metabolic pathways in cancer cells (Li et al, 2017). Among the factors that have not previously been associated with CLL we found several TFs significantly higher in U-CLL that are involved in the regulation of the circadian clock (i.e., BMAL1, CLOCK, and NR1D1), which has recently been proposed as a hallmark of cancer (El-Athman and Reló gio, 2018).…”
Section: Conceptual Derivation Of Tf Activity and Classification Of Tmentioning
confidence: 77%
“…which coactivate NF-kB-dependent survival signaling in CLL (Minami et al, 2010) and the GATA family, known to prime hematopoietic stem cells (HSCs) toward the lymphoid lineage and to increase self-renewal of the stem cells in CLL (Kikushige et al, 2011). We also found the EGR family, which are implicated in aberrantly hypomethylated CpG sites in CLL (Oakes et al, 2016); Gli1, which is part of the Hedgehog signaling pathway that regulates apoptosis, thereby supporting survival of M-CLL cells (Kern et al, 2015); and PPARD, which has recently been linked to M-CLL through its effect on metabolic pathways in cancer cells (Li et al, 2017). Among the factors that have not previously been associated with CLL we found several TFs significantly higher in U-CLL that are involved in the regulation of the circadian clock (i.e., BMAL1, CLOCK, and NR1D1), which has recently been proposed as a hallmark of cancer (El-Athman and Reló gio, 2018).…”
Section: Conceptual Derivation Of Tf Activity and Classification Of Tmentioning
confidence: 77%
“…Regarding PPAR-delta, it was reported that genetic knockdown of the receptor promotes colon cancer growth by decreasing differentiation, increasing proliferation and vascular endothelial growth factor expression in cancer cells [ 24 ]. The receptor could also promote breast cancer and leukemic cell survival cultured under unfavorable metabolic conditions [ 25 , 26 ]. Contrary to these reported PPAR-delta oncogenic effects, studies have also shown possible tumor suppression actions by PPAR-delta.…”
Section: Discussionmentioning
confidence: 99%
“…Various kinds of harsh conditions were tested: low glucose, hypoxia, exposure to glucocorticoids, and cytotoxic agents. In any case, the response of tumor cells was to improve antioxidant activity and make better use of energy supplies through a proper metabolic pathway [ 186 ]. More recently, the involvement of PPARβ/δ signaling in the survival of CLL cell lines was reported.…”
Section: Pparsmentioning
confidence: 99%